2022
DOI: 10.2196/27775
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mobile Patient-Reported Outcomes Version of the Common Terminology Criteria for Adverse Events Administration System to Capture Postradiation Toxicity in Oncology: Usability and Feasibility Study

Abstract: Background Accurate self-reported symptomatic toxicity documentation via the Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) is essential throughout cancer treatment to ensure safety and understand therapeutic efficacy. However, the capture of accurate toxicities from patients undergoing radiation therapy is challenging because this is generally provided only at the time of scheduled visits. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…2021 [ 37 ] ePROs in follow-up 8 weeks after RT (biweekly questionnaires) (LogPAL developed by Northwell Health Inc, Lake Success, USA) Single arm 38 Head and neck cancer patients receiving RT/RCT (curative) Feasible, regularly used, and accepted (73.2% questionnaires completed) Yes (iOS) Underwood et al. 2022 [ 39 ] Assessment of patient-related outcome after RT (“say all your symptoms” and symptom tracking CTCAE; mPROS app) Single arm 25 Patients receiving RT to head and neck, breast and pelvic areas Usable and feasible tailored assessment for patients to report symptomatic toxicities No Wöller et al. 2022 a [ 46 ] Follow-up app (Myoncare app, Oncare) Single arm 38 Prostate and breast cancer receiving radiotherapy (curative) For breast cancer patients: Interest in new communication with HCP (preliminary results) Yes (iOS and Andoid) Wong et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2021 [ 37 ] ePROs in follow-up 8 weeks after RT (biweekly questionnaires) (LogPAL developed by Northwell Health Inc, Lake Success, USA) Single arm 38 Head and neck cancer patients receiving RT/RCT (curative) Feasible, regularly used, and accepted (73.2% questionnaires completed) Yes (iOS) Underwood et al. 2022 [ 39 ] Assessment of patient-related outcome after RT (“say all your symptoms” and symptom tracking CTCAE; mPROS app) Single arm 25 Patients receiving RT to head and neck, breast and pelvic areas Usable and feasible tailored assessment for patients to report symptomatic toxicities No Wöller et al. 2022 a [ 46 ] Follow-up app (Myoncare app, Oncare) Single arm 38 Prostate and breast cancer receiving radiotherapy (curative) For breast cancer patients: Interest in new communication with HCP (preliminary results) Yes (iOS and Andoid) Wong et al.…”
Section: Resultsmentioning
confidence: 99%
“…As described in Tables 1 and 2 in detail, most patient-centered studies were single-arm studies or descriptive in nature. Overall, those studies showed high compliance [ 20 , 31 , 32 ], high acceptance [ 22 , 23 , 29 , 33 – 37 ], effectiveness [ 28 ], satisfaction [ 31 ], usability [ 29 , 38 , 39 ], simplicity [ 38 ], and feasibility [ 12 , 25 , 32 , 35 – 37 , 39 ]. The randomized two-arm studies analyzing the impact of an app on the standard of care showed a significant reduction in adverse effects in head and neck cancer patients [ 13 , 15 , 17 ] and prostate cancer patients undergoing RT [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have investigated the potential advantages of using mobile technologies in healthcare delivery and have found them to be promising 26. Various forms of healthcare information technology have been employed in the detection, management and follow-up of AEs 27 28. Text mining has been used to detect AEs based on data-driven methods, including spontaneous warning and reporting systems 29.…”
Section: Introductionmentioning
confidence: 99%
“… 26 Various forms of healthcare information technology have been employed in the detection, management and follow-up of AEs. 27 28 Text mining has been used to detect AEs based on data-driven methods, including spontaneous warning and reporting systems. 29 Commonly, AEs are characterised as a text classification problem, where a piece of text, either an entire document or its part, is mapped to one or more predefined classes that correspond to a type of AE or its property.…”
Section: Introductionmentioning
confidence: 99%